Septin Organization and Functions in Budding Yeast - Glomb, Oliver; Gronemeyer, Thomas (Frontiers in Cell and Developmental Biology, 2016)
The septins are a conserved family of GTP-binding proteins present in all eukaryotic cells except plants. They were originally discovered in the baker's yeast Saccharomyces cerevisiae that serves until today as an important model organism for septin research. In yeast, the septins assemble into a highly ordered array of filaments at the mother bud neck. The septins are regulators of spatial compartmentalization in yeast and act as key players in cytokinesis. This minireview summarizes the recent findings about structural features and cell biology of the yeast septins.